UPAYA AMERIKA SERIKAT DALAM MENJAGA KEAMANAN NASIONAL DARI CYBER WAR TAHUN 2009-2013 - Setyasih Harini, Achmad Sholeh Abubakar, Halifa Haqqi & (Transformasi, 2015)
The evolution of Information Technology of the 21st century growing increasingly. Cyberspace has become into a new arena in the dynamics of International relations. The United States notice a ―Wake-up Call‖ when The hacking of military base in the Middle East in 2008 and NASA's Jet Propulsion Laboratory in China's Internet Protocol address in 2012. This research focuses about the effort of The United State’s National Security of Cyber War in 2009-2013 by President Obama. This efforts it’s to response cyber attack conducted by the State or cyber terrorism.This research’s objective was to understand cyber security of the United State by President Obama in 2009 to 2013 against the threats of cyber war to protect the national interest in this case about the power of cyber security. The concept of national security and cyber security were used for further discussion. This descriptive analytical research used secondary data sources while its data collecting technique was library research. Data analysis technique included data reduction, data display, conclusions and verification. The results of this research indicate that the efforts made by President Obama in The United States cyber security in political and economic sector by increasing military resistance and technology, cyber diplomacy and keeping The Critical Infrastructure.Keywords : cyber security, cyber war, national security, The United States